CONTRIBUTIONS OF NURSES IN BASIC RESEARCH: DRESSING FIXATION MODEL FOR EXCISIONAL CUTANEOUS WOUNDS OF MICE (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: validate method of fixation of dressings on excisional cutaneous wounds of mice. Method: preclinical study. Sample made up of animals of the C57BL/6 strain, which had two excision wounds made in the dorsal region. Different methods and products, widely accepted in clinical practice, for fixing dressings in the animal model were evaluated. The evaluated outcomes were the length of stay of the dressing and the occurrence of adverse events. Results: crepe bandage, microporous tape and self adhesive bandage had a shorter residence time when compared to polyurethane film. This, in turn, varied the time when comparing different marks (E, F, G and H) and number of turns around the animal’s body. With 1 lap, the time varied from